PERSEPSI TENTANG PENGUATAN DARI GURU DAN PERHATIAN ORANG TUA DENGAN HASIL BELAJAR - Pebriza Helmi; Eswendi .; Abd. Hafiz (Universitas Negeri Padang, 2012)
Abstract The objective of this research is to test the relationship of student perception about: (1) the giving of reinforcement from teacher with the students’ study result of fine art, (2) the parents’ attention with the students’ study result of fine art, (3) the giving of reinforcement from teacher and the parents’ attention with the students’ study result of fine art. The source of data of this research was the students as the sample of the research. The data collected by using the observation and questionnaire technique. The result of the research were (1) there is the significant relationship between reinforcement from teacher to students’ result of study of art with the rate of significant 0,000 < α = 0,05, (2) there is the significant relationship between the parents’ attention to the students’ result of study of art with the rate of significant 0,000 < α = 0,05, and (3) there is the significant relationship between reinforcement from teacher and the parents’ attention to students’ result of study of art. Kata kunci: persepsi, penguatan, perhatian, hasil belajar